Designing E-Learning Services: A Case Study - Yang, Shanshan; Joy, Mike (International Journal of Advanced Corporate Learning (iJAC), 2009)
Recently, increasing numbers of e-learning tools have been developed. However, the benefits of these tools cannot be fully used as they typically operate separately and do not communicate with each other. It is necessary to develop a solution to redeploy existing tools, and create new tools, in a more effective way. Our approach is to link and manage these e-learning tools together, by grouping the tools together and presenting them as a set of e-learning services, implemented using service technologies. In this paper, we propose a set of e-learning services, together with the approach we have adopted to develop them, which are developed based on a case study.